Hear the beat: decellularized mouse heart regenerated with human induced pluripotent stem cells. (February 2014) - Lin, Bo; Lu, Tung-Ying; Yang, Lei
<x xml:space="preserve">Abstract</x> Heart tissue engineering holds a great potential for human heart disease therapy. Regeneration of whole biofunctional human heart is the ultimate goal of tissue engineering. Recent advances take the first step towards whole heart regeneration. However, a substantial amount of challenges have to be overcome.